Ecological risk assessment of oil-gas fields development in Kazakhstani sector of the Caspian sea (Journal of Geography and Environmental Management, 2018)
This article provides for determination of ecological risk associated with offshore drilling operations elated todrilling of offshore wells in Kazakhstani sector of the Caspian Sea.